A history of the world in sixteen shipwrecks - Gordon, Stewart, 1945- (ForeEdge, 2015)
"Shipwrecks as hidden windows on the history of globalization. Roman triremes of the Mediterranean. The treasure fleet of the Spanish Main. Great ocean liners of the Atlantic. Stories of disasters at sea fire the imagination as little else can, whether the subject is a historical wreck--the Titanic or the Bismark--or the recent capsizing of a Mediterranean cruise ship. Shipwrecks also make for a new and very different understanding of world history. A History of the World in Sixteen Shipwrecks explores the ages-long, immensely hazardous, persistently romantic, and still-ongoing process of moving people and goods across far-flung maritime worlds. Telling the stories of ships and the people who made and sailed them, from the earliest ancient-Nile craft to the Exxon Valdez, A History of the World in Sixteen Shipwrecks argues that the gradual integration of localized and separate maritime regions into fewer, larger, and more interdependent regions offers a unique window on world history. Stewart Gordon draws a number of provocative conclusions from his study, among them that the European 'Age of Exploration' as a singular event is simply a myth--many cultures, east and west, explored far-flung maritime worlds over the millennia--and that technologies of shipbuilding and navigation have been among the main drivers of science and technology throughout history. Finally, A History of the World in Sixteen Shipwrecks shows in a series of compelling narratives that the development of institutions and technologies that made terrifying oceans familiar, and turned unknown seas into sea-lanes, profoundly matters in our modern world"--Publisher's website